Effect of Different Preys on Certain Biological Characteristics of Green Lacewing, Chrysoperia carnea (Stephens) (Neuroptera: Chrysopidae) under Laboratory Conditions - Rana, L.B.; Mainali, R.P.; Regmi, H.; Rajbhandari, B.P. (Journal of the Plant Protection Society, 2020)
Abstract available with the full text.